Pertanggungjawaban Negara terhadap Pencemaran Minyak West Atlas Montara di Wilayah Laut Indonesia ditinjau dari UNCLOS 1982 - Yusnia Tika Safitri; Mahendra Putra Kurnia; Rika Erawati (Fakultas Hukum Universitas Mulawarman, 2020)
Hydrocarbon oil and gas leakage due to explosion in The Montana Well Head Platform (PTTEP Australasia at Blok West Atlas) Australian waters (690 Km west of Darwin and 250 Km northwest of western Australia Truscott) with a spill estimate of 400 barrels/day (64 tons/day) resulted in cross-border pollution due to entering ZEE Indonesia. The purpose of this discussion is to study and analyze Thailand's position in the case of cross-border pollution due to leakage of Montara atlas oil wells in the Timor Sea. The writing method uses the type of doctrinal approach consistent with the 1982 perspective of the United Nations Convention on the Law of the Sea and relevant legal theories that will be used and constructed with the principles of legal law, principles, and doctrine. Based on Article 139 Paragraph (1) of 1982 UNCLOS, the State shall be responsible for the activities carried out in the sea area, either by the participating State, individuals, or companies of the State or legal entities or individuals who have the nationality of their country. The peaceful settlement of disputes chosen by the disputing parties can be carried out, as stipulated in Chapter XV Article 279-293 of UNCLOS 1982. The settlement of this dispute can be carried out, provided it does not cause more significant harm to the people of East Nusa Tenggara, especially the people of Rote Island. Keywords: pollution, cross border, responsibility